Induction Motors Stator Fault Analysis based on Artificial Intelligence - Hussein Taha Hussein; Mohamed Ammar; Mohamed Moustafa Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This article presents a method for fault detection and diagnosis of stator inter-turn short circuit in three phase induction machines. The technique is based on the stator current and modelling in the dq frame using an Adaptive Neuro-Fuzzy artificial intelligence approach. The developed fault analysis method is illustrated using MATLAB simulations. The obtained results are promising based on the new fault detection approach.